ACCOUNTING REPORTS FOR MANAGEMENT INVESTMENT COMPANIES. - Smith, Frank P. (The Accounting Review, 1940)
The article focuses on accounting reports for management investment companies in the U.S. In the past 15 years American investment trusts and investment companies have developed from a little-known type of financial institution to the stature of an established industry. In this relatively short period the new industry has been faced with the varied problems of developing investment, trading and dividend policies, reporting techniques and accounting principles and procedures. It is not surprising that the same rate of progress was not maintained in all fields but it is unfortunate that one of the early lags appeared in the field of reporting techniques. In their early years, American investment companies were influenced to some extent by experiences of British investment trusts. In addition, American companies were faced early in the development of the industry with the accounting and reporting problems arising from a very rapid increase in size, rapidly increasing stock prices and subsequent drastic breaks in stock prices. The rapid increase in the importance of American investment companies can be indicated by tracing the number of companies in existence and assets of these companies.